Linking Oxidative Stress and Proteinopathy in Alzheimer's Disease - Chanchal Sharma; Sang Ryong Kim (MDPI AG, 2021)
Proteinopathy and excessive production of reactive oxygen species (ROS), which are the principal features observed in the Alzheimer's disease (AD) brain, contribute to neuronal toxicity. β-amyloid and tau are the primary proteins responsible for the proteinopathy (amyloidopathy and tauopathy, respectively) in AD, which depends on ROS production; these aggregates can also generate ROS. These mechanisms work in concert and reinforce each other to drive the pathology observed in the aging brain, which primarily involves oxidative stress (OS). This, in turn, triggers neurodegeneration due to the subsequent loss of synapses and neurons. Understanding these interactions may thus aid in the identification of potential neuroprotective therapies that could be clinically useful. Here, we review the role of β-amyloid and tau in the activation of ROS production. We then further discuss how free radicals can influence structural changes in key toxic intermediates and describe the putative mechanisms by which OS and oligomers cause neuronal death.